"At the Shores of the Sky" Asian Studies for Albert Hoffstädt - Kroll, Paul W.; Silk, Jonathan A. (Sinica Leidensia, 2020)
Albert Hoffstädt, a classicist by training and polylingual humanist by disposition, has for 25 years been the editor chiefly responsible for the development and acquisition of manuscripts in Asian Studies for Brill. During that time he has shepherded over 700 books into print and has distinguished himself as a figure of exceptional discernment and insight in academic publishing. He has also become a personal friend to many of his authors. A subset of these authors here offers to him in tribute and gratitude 22 essays on various topics in Asian Studies. These include studies on premodern Chinese, Indian, Japanese, and Korean literature, history, and religion, extending also into the modern and contemporary periods. They display the broad range of Mr. Hoffstädt's interests while presenting some of the most outstanding scholarship in Asian Studies today. Readership: All interested in Asian humanities, premodern or modern.